Monitoring expenditure and utilisation of medicines in the European Union. A public health approach (Italian Journal of Public Health, 2006)
Background Thousands of medicinal products are licensed in the European Union Member States.This large quantity of medicines has an important impact on individual and public health but the information available on the licensed medicines, their clinical properties, prices, utilisation and expenditure is difficult to retrieve. Thus there is a need for monitoring the price, expenditure and utilisation of medicines and their impact on the population’s health. For these reasons the European Commission funded a project to define a set of indicators and to build a European database of medicines.Methods A collaboration of academics and government agencies was formed to undertake the project which aims to fill the information gap on medicines in Europe by identifying the available data sources, defining a set of EU pharmaceutical indicators, and building a European database of medicines available on the internet.Results The project has formed a Library of European Union Pharmaceutical Indicators. This includes recommendations for national registers (to produce valid and comparable data), and a set of indicators (price, expenditure, utilisation) for monitoring pharmaceutical policies. Moreover, the project has built a (beta version) database of licensed medicines in Europe, which can be freely accessed on the internet.The database provides, in a simple manner, useful information difficult to retrieve by other sources.Conclusions The EURO-MED-STAT project has defined a set of indicators to monitor the utilisation and expenditure of medicines from a public health perspective. It has also proven that a European database of medicines is feasible and can provide useful information to stakeholders.
Keywords: Medicines; utilisation; ATC/DDD; public health